Dynamics of respiratory indicators in patients with bilateral destructive tuberculosis after surgical treatment using staged bilateral extrapleural pneumolysis with silicone plombage - D. V. Donchenko; M. I. Chushkin; R. V. Tarasov; E. V. Krasnikova; M. V. Chashchina; M. A. Bagirov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2024)
Introduce. Patients with a high prevalence of the process and extensive destruction of the pulmonary parenchyma have reduced lung reserves, which limits the use of resection interventions.Objective. To study the dynamics of respiratory function indicators in patients with bilateral widespread destructive tuberculosis during surgical treatment using staged bilateral extrapleural pneumolysis with silicone plombage (ESP).Object and methods. The main group consisted of 11 patients who underwent surgical treatment using staged bilateral ESP. The comparison group included 8 patients with bilateral widespread destructive pulmonary tuberculosis who underwent consecutive bilateral lung resections with a volume of more than 3 segments. The dynamics of respiratory function indicators were studied 3–5 weeks after surgery.Results. In the main group, after stage-by-stage surgical treatment, the FVC index decreased by 0.9 ± 0.6 liters, while in the comparison group by 1.3 ± 0.7 liters (p < 0.01). The index of FEV1 in patients of the main group decreased by 0.5 ± 0.5 liters, and in the comparison group by1 ± 0.3 liters (p < 0.01).Conclusion. Staged surgical treatment with the use of bilateral ESP is accompanied by a significantly smaller decrease in functional parameters and can be used in patients with widespread bilateral destructive tuberculosis with low respiratory function.